Estimated use of abacavir among adults and children enrolled in public sector antiretroviral therapy programmes in Gauteng, South Africa - D Evans; M Maskwe; C Heneger; I Sanne (AOSIS, 2012)
In South Africa, abacavir (ABC) is currently recommended as part of first- and second-line antiretroviral therapy (ART) for HIV-positive paediatric patients. Concerns about overprescribing of the drug, particularly to adults, led to an analysis of ABC use in public sector ART programmes. We investigated current prescription of the drug to adults and children accessing ART in 4 public sector programmes across Gauteng Province, South Africa. ABC was almost exclusively prescribed to children initiating ART and adults requiring regimen changes due to drug toxicities. Patterns of ABC use among HIV-positive paediatric patients followed national ART treatment guidelines on the application of the drug. Although ABC is commonly used in the private sector for adults, the current national ART treatment guidelines for adults and adolescents should include ABC as an alternative to standard first- or second-line ART.